Subdiaphragmatic vagal afferent nerves modulate visceral pain - Chen, S. L. (2008)
Activation of the vagal afferents by noxious gastrointestinal stimuli suggests that vagal afferents may play a complex role in visceral pain processes. The contribution of the vagus nerve to visceral pain remains unresolved. Previous studies reported that patients following chronic vagotomy have lower pain thresholds. The patient with irritable bowel syndrome has been shown alteration of vagal function. We hypothesize that vagal afferent nerves modulate visceral pain. Visceromotor responses (VMR) to graded colorectal distension (CRD) were recorded from the abdominal muscles in conscious rats. Chronic subdiaphragmatic vagus nerve sections induced 470, 106, 51, and 54% increases in VMR to CRD at 20, 40, 60 and 80 mmHg, respectively. Similarly, at light level of anesthesia, topical application of lidocaine to the subdiaphragmatic vagus nerve in rats increased VMR to CRD. Vagal afferent neuronal responses to low or high-intensity electrical vagal stimulation (EVS) of vagal afferent Aδ or C fibers were distinguished by calculating their conduction velocity. Low-intensity EVS of Aδ fibers (40 μA, 20 Hz, 0.5 ms for 30 s) reduced VMR to CRD at 40, 60, and 80 mmHg by 41, 52, and 58%, respectively. In contrast, high-intensity EVS of C fibers (400 μA, 1 Hz, 0.5 ms for 30 s) had no effect on VMR to CRD. In conclusion, we demonstrated that vagal afferent nerves modulate visceral pain. Low-intensity EVS that activates vagal afferent Aδ fibers reduced visceral pain. Thus EVS may potentially have a role in the treatment of chronic visceral pain.